Strategy for a portuguese wine in China: the case-study of Couteiro-mor - Anselmo, Cátia Alexandra Arez de Sousa (2017)
This master thesis is a company project developed with the collaboration of Couteiro-Mor, a Portuguese wine company from the region of Alentejo (Herdade do Menir, Montemor-oNovo). In the past years, although the company has been growing there is a great business opportunity outside of Portugal that Couteiro-Mor can no longer ignore. In this sense, this case-study aims to propose to Couteiro-Mor a marketing strategy and an expansion plan to enter the Chinese wine market. China is currently playing an important role in the global economy and has a large part of its population increasing their interest for wine, especially imported wine. Therefore, in order to help the company succeed in this market the first approach is to develop an analysis of the macro environment, an internal analysis of the company and a competitive analysis. Then, it is suggested the entry mode in the country (export) and a marketing plan for approaching the Chinese market in the next year. Lastly, it is suggested an implementation and control of the marketing plan